The Relationship Of House Physical Environment With Tuberculosis In The Jaten Ii Health Center Of Karanganyar District - Mindiharto, Sestiono (Universitas Muhammadiyah Gresik, 2020)
Tuberculosis is a major health problem worldwide. Tuberculosis in Indonesia is number three cause of death after cardiovascular disease and respiratory disease that attacks all age groups. To determine the relationship between the physical environment with the incidence of Tuberculosis in Jaten II District Health Center, Karanganyar District. Analytical, cross sectional, total respondent population, purposive sampling, questionnaire sheet, frequency distribution table, cross tabulation and chy square test ɑ = 0.05 Most of the houses of respondents who had poor ventilation were 33 people (86.84%), houses with bad temperatures 27 (71.05%) people, respondents with poor housing density 31 (81.57%) people, house construction bad 30 (78.94%) people. The test results of chy square Ρ <α = 0.010 <(0.05) with an odds ratio of 10.8. There is a sanitation relationship in the home environment with the incidence of Tuberculosis in the Jaten II Public Health Center of Karanganyar Regency. Ρ <α = 0.010 <(0.05) with an odds ratio of 10.8.